Successful multimodality treatment of anorectal melanoma after wide local excision: a case report - Liang, Zhao; Zongjian, Liu; Chunlai, Pan; Lihua, Wang; Hexue, Yuan (Frontiers in Oncology, 2025)
ObjectiveThe purpose of this case report is to explore the efficacy of comprehensive treatment of anal melanoma and to provide reference for the treatment of anal melanoma.MethodsA rare case of anorectal melanoma was collected. After local excision, the patient was treated with a combination of the anti-vascular survival drug bevacizumab, anti-PD-1 immunotherapy and other treatments, and the patient’s prognosis and survival were observed.ResultsA 61-year-old male was admitted to the hospital with complaints of anal prolapse and a mass appearing after defecation, accompanied by intermittent bloody stool for one week. He was initially diagnosed with mixed hemorrhoids, and a hemorrhoidectomy was performed. Postoperative pathology confirmed malignant melanoma with negative surgical margins, leading to a clinical diagnosis of AM. Following local excision surgery, the patient underwent targeted therapy with bevacizumab, anti-PD-1 immunotherapy and other treatments. After nearly three years of follow-up, the patient remained in good condition and while follow-up CT and MRI revealed some enlarged lymph nodes, there were no symptoms or signs of systemic metastasis.ConclusionThe combination of local resection of the primary lesion with bevacizumab targeted therapy and anti-PD-1 immunotherapy is feasible and can substantially improve the survival time of patients with AM.